In Memoriam - Prof. Emeritus Doris A. Graber - Capelos, Tereza (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2018)
On February 17th 2018, our international academic community lost a great mind, an inspirational role model, a pioneer colleague, that shaped our field in unique ways. Professor Emeritus Doris a. Graber (University of Illinois in Chicago) authored over 15 textbooks and 50 book chapters and lectures in political science and political commu- nication, focusing particularly on the psychological antecedents and consequences by which media content shapes political audiences’ prefe- rences. Her theoretical and empirical contributions, work that spans a rich academic career of over 70 years, cemented our academic re- search practices and inspired many generations of scholars.